Pengaruh Kualitas Informasi terhadap Keputusan Memilih Objek Wisata dengan Trust sebagai Variabel Intervening: Studi pada Followers Akun Instagram @folkindonesia - Husnul Fuad Maulana (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
The purpose of this study is to analyze and discuss the influence of information quality on the decision to choose attractions with trust as an intervening variable. The sampling technique used was non-probability sampling with a purposive sampling method. The population in this study is the age category 17-40 years which is infinite who has become followers of @folkindonesia with a sample of 220 respondents. The questionnaire was distributed online then measured by the Likert scale and path as data analysis. The results showed that the quality of information and trust significantly influence the decision to choose attractions. But not with the information’s quality which doesn’t have a significant direct effect without trust as a mediator on the decision to choose a tourists destination. Furthermore, this study also found that information quality has a significant effect on trust. Meanwhile, based on the Sobel test results trust variable succeeded in mediating the relationship between the information quality variable on the decision to choose a tourists destination